Analysis of Risk Factors for Dengue Hemorrhagic Fever in Children: An Observational Study in Batang Regency, Indonesia - Jaya Maulana; Restu Mastuti, Dewi Nugraheni; Yasmin Meida (Scientific Journal of Pediatrics, 2024)
Dengue hemorrhagic fever (DHF) is a significant public health problem in Indonesia, including in Batang Regency. This study aims to analyze the risk factors associated with the incidence of dengue fever in children in Batang Regency, Indonesia. A cross-sectional observational study was conducted on 258 child subjects in Batang Regency. Data was collected through structured interviews with parents or guardians, direct observation of the home environment, and laboratory tests to confirm the diagnosis of dengue fever. Data analysis included univariate, bivariate (Chi-square test), and multivariate (logistic regression) analyses to identify independent risk factors. Univariate analysis showed a relationship between the incidence of dengue fever and age, gender, parental education, parental occupation, residential density, presence of mosquito larvae in water reservoirs, habit of hanging clothes, history of mosquito bites, and nutritional status. Bivariate analysis identified several statistically significant risk factors, including high residential density (OR=2.87; 95% CI: 1.65-5.01), presence of mosquito larvae (OR=3.21; 95% CI: 1.89-5.45), habit of hanging clothes (OR=2.87; 95%CI:1.32-5.21), and history of mosquito bites (OR=2.54; 95%CI: 1.48 -4.36). Multivariate analysis confirmed that high residential density and the presence of mosquito larvae were independent predictors of dengue incidence. High residential density and the presence of mosquito larvae in the home environment are the main risk factors for the incidence of dengue fever in children in Batang Regency. Public health interventions that focus on vector control and improving environmental sanitation are critical to reducing the dengue burden in this area.